Sugarcane Production Efficiency: A Case Study on PTPN X Partner Farmers - Rosidah, Afifatur; Irham; Masyhuri; Perwitasari, Hani (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The low production and productivity of sugarcane is a problem for the sugar industry in Indonesia, while the demand for sugar increases yearly. One of the efforts to increase sugarcane productivity is improving the efficiency of sugarcane farming. Appropriate farming efficiency and identification of inefficient resources can increase farming productivity. PTPN X, as a company engaged in the sugarcane plantation and sugar industry, obtains most raw materials from partner farmers. This study aimed 1) to determine the technical, allocative, and economic efficiency of sugarcane farming and 2) to analyze the managerial characteristics of farmers that affect the technical inefficiency of sugarcane farming. This study uses the stochastic frontier Cobb-Douglas production function approach and the dual frontier cost function. The results show that the average level of sugarcane farming's technical, allocative, and economic efficiency are 0.762; 1.315; and 0.976, respectively. The average level shows that sugarcane farming has been technical, allocative, and economically efficient. Farmers' managerial characteristic that affects technical inefficiency is the farmer's education level. The study suggests reducing the effect of inefficiency by taking higher education. Farmers with a low technical efficiency value can adopt the use of inputs by farmers with a higher value. Keywords: technical efficiency, allocative, economic, sugarcane